Health and well-being implications surrounding the use of wearable GPS devices in professional rugby league: A Foucauldian disciplinary analysis of the normalised use of a common surveillance aid. Issue 2 (December 2016) - Jones, Luke; Marshall, Phil; Denison, Jim
Abstract: Wearable GPS tracking devices have become commonplace coaching aids across professional field sports to enhance sports performances and reduce injury rates, despite the implications of the technology being poorly understood. This study looked at how GPS devices are used and the impact constant surveillance has upon the physical, psychological, and emotional health of rugby football workers. The disciplinary analysis of Michel Foucault was used to investigate how British Super League teams use wearable GPS technology, to investigate the dominant 'truth' that promotes surveillance technologies as 'universally beneficial' to athlete sports performance, health and well-being. Data was drawn from semi-structured interviews with three performance analysts/strength and conditioning coaches at three different Super League clubs across the North of England. Participants confessed data generated from wearable GPS is often totally ignored, despite being specifically produced to protect athlete health and wellbeing. When used, GPS data can become a 'disciplinary tool' to normalise and coerce players to comply with potentially unhealthy physical and psychological demands of a professional playing career. Importantly, regardless of how GPS data was used, the employment of wearable GPS devices was constantly and rigorously implemented. The constant surveillance experience by working players, when mismanaged or adopted as a coercive disciplinary tool, magnifies the uncertainty and fear of failure central to the predominant challenges that arise during a working football career. This leads to the acceptance of problematic norms damaging to physical, psychological, and emotional health. If GPS or other surveillance based performance analysis technologies are to be used in sport, coaches need to regulate or re-think their day-to-day use to avoid creating new harms to athlete health and well-being.